Estrategia didáctica el dado preguntón y las tarjetas respondonas para mejorar la comprensión de textos en estudiantes de primaria - Castillo Rodriguez, Leonidas Julian (2021)
The present work aims to improve the comprehension of texts in primary level students by applying the didactic strategy "the given question and the answering cards" seeking to contribute to the solution of educational problems in which students do not understand what they they read. The use of the didactic strategy "the given question and the answering cards" makes it possible to develop the comprehension of texts in a dynamic way in the students using recreational resources and strengthening the processes of socialization and communication. Therefore, it is also constituted as an innovative strategy that allows achieving higher performances in the competences of the communication area. It is concluded that the didactic strategy "the given question and the answering cards" allows to improve reading comprehension in primary education students because it is a fun, stimulating, creative and pertinent strategy that motivates students and allows them to better understand what is they read.